2016
DOI: 10.1515/tjj-2015-0033
|View full text |Cite
|
Sign up to set email alerts
|

Full-Range Mathematical Modeling of Turboshaft Engine in Aerospace

Abstract: In this paper, an approximate computation method of low-speed component characteristics in aeroengine is used and full-range component characteristics is obtained by combining experimental data above idle. Moreover, based on components matching method and variable specific heat method, a full-range static and dynamic mathematical model of turboshaft engine is built, including start-up state. And the numerical simulation result of the engine whole working process is also showed in this paper. The comparison res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Figure 20 shows THD (Total Harmonic Distortion), a measurement of the harmonic distortion present in a signal and is defined as the ratio of the sum of the powers of all harmonic components to the power of the fundamental frequency, of extracted current from the network. THD value is obtained as: (15) where I 1 is the main component of current and I k is the kth harmonic component of current. In this section, based on the speed reference curve, the set of network-drive-starter motor-gas turbine is simulated.…”
Section: Analysis Of Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 20 shows THD (Total Harmonic Distortion), a measurement of the harmonic distortion present in a signal and is defined as the ratio of the sum of the powers of all harmonic components to the power of the fundamental frequency, of extracted current from the network. THD value is obtained as: (15) where I 1 is the main component of current and I k is the kth harmonic component of current. In this section, based on the speed reference curve, the set of network-drive-starter motor-gas turbine is simulated.…”
Section: Analysis Of Simulation Resultsmentioning
confidence: 99%
“…A case study focusing on the effects of ground starts was added that compared findings from engine dry crank with those of simulations, corroborating the ability of simulation for estimation of proper trends. Sheng et al [15] employed an inexact computational approach regarding low-speed part behavior in aeroengines so as to obtain comprehensive component characteristics with the aid of integrating empirical data above idle. The result was a turboshaft engine model that could consider the start-up state.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, an engine comprising of higher starter capacity is very beneficial in terms of fuel saving and preventing the hot parts of the engine from damage due to excessive fuel flow. Additionally, some other researchers have developed transient models for idle and sub-idle regimes for civil aero engines, such as sheng et al [ 87 ], who suggested a stage stacking method for extrapolation of low speed region in order to simulate a full rage startup transient model for a turboshaft engine. Similarly, Kim et al [ 88 ] have used a thermodynamic model for a triple-shaft turbofan engine in order to simulate three different kind of startup regimes, i.e., wind milling, sub-idle and idle to maximum power ranges.…”
Section: Classifications Of Transient Regimes In Igtmentioning
confidence: 99%
“…The following are mathematical models for each of them as well as atmospheric environment. 36 Atmospheric environment. The effects of atmospheric pressure and temperature on flight conditions are considered here.…”
Section: Mathematical Model For a Turboshaft Aeroenginementioning
confidence: 99%